2015
DOI: 10.1186/s12860-015-0056-6
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone in osteogenic medium strongly induces adipocyte differentiation of mouse bone marrow stromal cells and increases osteoblast differentiation

Abstract: BackgroundOsteoblasts and adipocytes share a common mesenchymal stem cell origin. Therefore, it has been suggested that the accumulation of marrow adipocytes observed in bone loss is caused by a shift in the commitment of mesenchymal stem cells from the osteogenic pathway to the adipogenic pathway. Supporting this hypothesis the competition between adipogenic and osteogenic lineages was widely demonstrated on partially homogeneous cell populations. However, some data from mouse models showed the existence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 42 publications
3
102
0
1
Order By: Relevance
“…The gene expression of adipogenic‐related genes was higher in the sAD+ cells than in sOS+ cells, with the exception of the expression of LEP , which was downregulated in the sAD+ compared with sOS+ cells. This latter result may be explained as the effect of dexamethasone (present in both adipogenic and osteogenic medium used in the present study) that was shown to upregulate LEP (Ghali et al, ). Interestingly, sAD+ expressed the osteogenic‐related genes at the same ( RUNX2 , ALP , and bGLAP ) level as or higher ( IBSP ) than the sOS+ cells (Figure e).…”
Section: Resultsmentioning
confidence: 61%
“…The gene expression of adipogenic‐related genes was higher in the sAD+ cells than in sOS+ cells, with the exception of the expression of LEP , which was downregulated in the sAD+ compared with sOS+ cells. This latter result may be explained as the effect of dexamethasone (present in both adipogenic and osteogenic medium used in the present study) that was shown to upregulate LEP (Ghali et al, ). Interestingly, sAD+ expressed the osteogenic‐related genes at the same ( RUNX2 , ALP , and bGLAP ) level as or higher ( IBSP ) than the sOS+ cells (Figure e).…”
Section: Resultsmentioning
confidence: 61%
“…Aromatase is involved in the estrogen biosynthesis from C19 steroids that is regulated by vitamin D, testosterone, phytoestrogens as well as dexamethasone [33]. Dexamethasone was used as one component in our osteogenic and, to a higher concentration, in our adipogenic differentiation medium similar to other differentiation studies [15,16,34]. However, to date it is not known if addition of dexamethasone influences the expression of nAChR.…”
Section: Discussionmentioning
confidence: 97%
“…DEX was an anti-inflammatory drug, and was widely used in various serious disease (18). Study has reported that DEX could inhibit osteoblast differentiation (19,20). In this study, we aims to evaluate whether DEX supplementation could induce the similar effects in normal chondrocytes as LCPD chondrocytes.…”
Section: Discussionmentioning
confidence: 99%